2018
DOI: 10.1080/15226514.2017.1413332
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of toxic Cr (VI), Fe, and other heavy metals phytoremediation by the synergistic combination of native Bacillus cereus strain and Vetiveria zizanioides L

Abstract: Bioremediation of Cr (VI), Fe, and other heavy metals (HMs) through plant-microbes interaction is one of the efficient strategies due to its high efficiency, low cost, and ecofriendly nature. The aim of the study was to isolate, characterize, and assess the potential of rhizospheric bacteria to enhance growth and metal accumulation by the chromium hyperaccumulator Vetiveria zizanoides. The bacterial strain isolated from mine tailings was identified to be Bacillus cereus (T1B3) strain exhibited plant growth-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(27 citation statements)
references
References 47 publications
0
26
0
1
Order By: Relevance
“…Nayak et al [115] showed that the hyper-accumulating capability of Vetiveria zizanoides could be enhanced by inoculating the native V. zizanioides with Bacillus cereus T1B3 strain. Similarly, Colocasia esculenta showed effective removal of Cr(VI) in water from wetlands due to the high accumulation of Cr(VI) in the roots part compared to the other parts [116].…”
Section: Phytoremediation By Hyperaccumulating Plantsmentioning
confidence: 99%
“…Nayak et al [115] showed that the hyper-accumulating capability of Vetiveria zizanoides could be enhanced by inoculating the native V. zizanioides with Bacillus cereus T1B3 strain. Similarly, Colocasia esculenta showed effective removal of Cr(VI) in water from wetlands due to the high accumulation of Cr(VI) in the roots part compared to the other parts [116].…”
Section: Phytoremediation By Hyperaccumulating Plantsmentioning
confidence: 99%
“…Induced production of phosphate and Siderophores which helps in the phytoremediation of Cd [329] 12.…”
Section: Host Plants Pgrb Species Specific Functions Referencesmentioning
confidence: 99%
“…However, when the contact time is longer than 24 h, the influence of the Cr(VI) concentration becomes insignificant. The reasons may be as follows: (1) In the early stage, high concentration of Cr(VI) has a large negative effect on Bacillus cereus, such as oxidative stress, DNA and protein damage 37 ; (2) After a period of time, Bacillus cereus is resistant to Cr(VI) stress and restores activity. This also indicates that Bacillus cereus has good adaptability to high concentrations of Cr(VI).…”
Section: Resultsmentioning
confidence: 99%